2021
DOI: 10.1159/000514800
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Treatment of cT3 Rectal Cancer in a Prospective Multi-Center Observational Study: Can Neoadjuvant Chemoradiation Be Omitted in Patients with an MRI-Assessed, Negative Circumferential Resection Margin?

Abstract: <b><i>Background/Aim:</i></b> Neoadjuvant chemoradiation (nCRT) in rectal cancer is associated with significant long-term morbidity. It is unclear whether nCRT in resectable mesorectal fascia circumferential resection margin (mrCRM)-negative rectal cancer treated by adequate total mesorectal excision (TME) is beneficial. The aim was to determine if nCRT can be omitted in patients with MRI-assessed cT3 rectal cancer and a negative mrCRM undergoing good-quality TME. <b><i>Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
2
0
4
Order By: Relevance
“…Furthermore, patients with tumors with good prognostic features (cT2-3ab CRM − mrEMVI − tumors, regardless of cN-stage) could be safely treated with surgery alone, resulting in a 3% LR rate. Several studies thereafter confirmed that upfront TME surgery was associated with similarly low LR rates compared with n(C)RT as long as the MRF is free, although this might be debated for the distal tumors based on the OCUM trial …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with tumors with good prognostic features (cT2-3ab CRM − mrEMVI − tumors, regardless of cN-stage) could be safely treated with surgery alone, resulting in a 3% LR rate. Several studies thereafter confirmed that upfront TME surgery was associated with similarly low LR rates compared with n(C)RT as long as the MRF is free, although this might be debated for the distal tumors based on the OCUM trial …”
Section: Discussionmentioning
confidence: 99%
“…Chuyển mổ mở, (5). Đã mổ do bệnh ung thư khác, (6) "Nguồn: Glynne-Jones R -ESMO Clinical Guidelines (2017)" 4…”
Section: đặT Vấn đềunclassified
“…Phẫu tích 4 bình diện trực tràng: Lấy bỏ bán phần MTTT (dưới u 5cm) hoặc toàn bộ MTTT (dưới u ít nhất 2cm), (5). Bảo tồn thần kinh tự động vùng chậu, (6). Thực hiện miệng nối bằng máy khâu nối hoặc nối tay (7).…”
Section: Hội Chẩn đA Mô Thức: Sau Khi Có Kết Quảunclassified
See 1 more Smart Citation
“…Studies on quality assurance in clinical medicine, in particular, in “oncosurgery”, have a long tradition at the Magdeburg’s Institute of Quality Assurance in Operative Medicine (Otto von Guericke University; former scientific heads: Profs. Lippert and Gastinger) - see a selection in the reference list [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ], [ 6 ], [ 7 ].…”
mentioning
confidence: 99%